Bone Marrow-Derived Inducible Microglia-like Cells Promote Recovery of Chronic Ischemic Stroke Through Modulating Neuroinflammation in Mice - Bach Ngoc Nguyen; Tomoaki Kitamura; Shuhei Kobashi; Makoto Urushitani; Tomoya Terashima (Biomedicines)
Background: Chronic ischemic stroke presents a significant challenge in neurology, with limited therapeutic options available for long-term recovery. During cerebral infarction, anti-inflammatory phenotype microglia/macrophages produce anti-inflammatory cytokines and neurotrophic factors that facilitate the process of brain repair. However, obtaining sufficient anti-inflammatory microglia/macrophages from the human central nervous system is challenging. Bone marrow-derived inducible microglia-like cells (BM-iMGs) with an anti-inflammatory microglial phenotype were explored to induce neuroprotective properties. Here, we transplanted BM-iMGs into the brain of middle cerebral artery occlusion (MCAO) model male mice to explore their potential for treating chronic ischemic stroke. Methods: Bone marrow-derived mononuclear cells (BM-MNCs) were isolated from green fluorescent protein mice and incubated with granulocyte–macrophage colony-stimulating factor (GM-CSF) and IL-4 to induce BM-iMGs with an anti-inflammatory phenotype. BM-iMGs were transplanted into the brains of mice on day 14 after MCAO, and behavioral tests, histology, cerebral blood flow, and gene expression were evaluated. Results: An intracranial injection of BM-iMGs promoted neurobehavioral recovery, reduced neuronal cell loss, suppressed neuroinflammatory astrocytic and microglial responses in the brain, and increased cortical surface cerebral blood flow in MCAO mice. Furthermore, neuroprotective genes were upregulated, whereas proinflammatory genes were downregulated. Conclusions: The intracranial injection of BM-iMG cells shows significant potential as a novel therapy for chronic ischemic stroke.